Preparation, Characterization and Utilization of Activated Carbon Prepared from Putrescible Vegetable Waste for the Removal of Malachite Green from its Aqueous Solution - Meena Sundari, P.; Senthamilselvan, K.; Madhava Krishnan, S.; Meenambal, T. (Asian Journal of Chemistry, 2014)
Activated carbon of high adsorption capacities and highly active surface properties were prepared from putrescible vegetable waste material. Chemical activation was done by impregnating the raw material with H3PO4 to get phosphoric acid activated carbon (PAAC). Phosphoric acid activated carbon was sieved to different particle sizes and particle size between 125-200 μm was utilized for adsorption studies. Physico-chemical properties of PAAC were analyzed to find out its adsorptive property. Porous nature of the activated carbon before and after adsorption was captured through scanning electron microscope. Surface area for PAAC was found to be 603.7 m2/g. Spectral studies like Fourier transform infrared spectrometry analysis, X-ray diffraction spectroscopy and SEM elemental analysis were done to characterize the carbon. The adsorption of malachite green from aqueous solution on PAAC was described by Langmuir, Freundlich and Dubnin-Radushkevich isotherms. All the three isotherms revealed that the adsorption of malachite green onto PAAC was favourable. It was found that PAAC follow pseudo second order kinetics for the adsorption of malachite green from its aqueous solution. Intraparticle diffusion model concluded that surface adsorption and it was concurrently operating during the malachite green and PAAC interactions. Results thus revealed that the phosphoric acid activated carbon prepared from putrescible vegetable waste could be effectively employed for cationic dye removal. The present work suggested a novel method for an effective solid waste management and their conversion into value added products.